BILANGAN KHROMATIK PEWARNAAN GRAF DALAM MENGOPTIMALKAN TEMPAT PENYIMPANAN BAHAN KIMIA - Eka Aprilia Suci Ananda; Yuni Listiana; Viktor Sagala (Jurnal Matematika Sains dan Teknologi, 2021)
Vertex coloring is a method giving colors to vertex in a graph, so that each neighborhood vertex has a different color. Chromatic numbers are the minimum number of colors that can be used to color the vertices on a graph G. The aim of this research is to optimize the storage of chemicals safely by applying the application of chromatic number of graph coloring and to determine whether the chemical storage in the laboratory is optimal or not. This study is using a qualitative observation research design. We use a graph coloring method to obtain optimal results. And we get data by observation, interview and documentation. The instrument that we used to collect data consist of chemical data form. The data analysis activity starts from collecting the lists names of chemicals until draw conclusions.The results of this study, using the Welch-Powell Algorithm we get the chromatic number is 4. So that by applying the chromatic number of graph coloring, we just need place chemical in the laboratory as many as 4 cabinets, so that the storage area more optimal laboratory compared to the previous storage area of ​​6 cabinets.